Prevalence and factors associated with xerostomia in patients hospitalized due AIDS-related complications - Jhonatan Yukio Naka; Adryano Arana Kamei; Vanessa C. Klamas; Mateus A. Ventura; Marcelo Morato; Rafael Z. Mobile; Antonio A. S. D. Lima (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction Xerostomia is a subjective sensation of dry mouth due to lack of saliva. The objective of this study was to investigate the prevalence and factors associated with the presence of hypo-salivation and xerostomia complaint in patients with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS)-related complications.